First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Widespread presence of potato virus Y in the main potato-producing region of Paraguay - Diana C. Zorrilla; Marcelo Alborno-Jover; Yerutí Mongelos-Franco; Blanca Coronel; Heron Kraide; Lino Ramirez-Ayala; Adans Colman; Jorge A. M. Rezende; Elliot W. Kitajima; Alfredo Gryciuk Almeida; Arnaldo Esquivel-Fariña (Journal of Plant Pathology, 2025)

Fire transforms effects of terrestrial subsidies on aquatic ecosystem structure and function - Christopher B. Wall; Cody J. Spiegel; Evelyn M. Diaz; Cindy H. Tran; Alexia Fabiani; Taryn Y. Broe; Elisabet Perez‐Coronel; Sara L. Jackrel; Natalie Mladenov; Celia C. Symons; Jonathan B. Shurin (Global Change Biology, 2024)
Fire can lead to transitions between forest and grassland ecosystems and trigger positive feedbacks to climate warming by releasing CO 2 into the atmosphere. Climate change is projected to increase the prevalence and severity of wildfires. However, fire effects on the fate and impact of terrestrial organic matter (i.e., terrestrial subsidies) in aquatic ecosystems are unclear. Here, we performed a gradient design experiment in freshwater pond mesocosms adding 15 different amounts of burned or unburned plant detritus and tracking the chronology of detritus effects at 10, 31, 59, and 89 days. We show terrestrial subsidies had time‐ and mass‐dependent, non‐linear impacts on ecosystem function that influenced dissolved organic carbon (DOC), ecosystem metabolism (net primary production and respiration), greenhouse gas concentrations (carbon dioxide [CO 2 ], methane [CH 4 ]), and trophic transfer. These impacts were shifted by fire treatment. Burning increased the elemental concentration of detritus (increasing %N, %P, %K), with cascading effects on ecosystem function. Mesocosms receiving burned detritus had lower [DOC] and [CO 2 ] and higher dissolved oxygen (DO) through Day 59. Fire magnified the effects of plant detritus on aquatic ecosystem metabolism by stimulating photosynthesis and respiration at intermediate detritus‐loading through Day 89. The effect of loading on DO was similar for burned and unburned treatments (Day 10); however, burned‐detritus in the highest loading treatments led to sustained hypoxia (through Day 31), and long‐term destabilization of ecosystem metabolism through Day 89. In addition, fire affected trophic transfer by increasing autochthonous nitrogen source utilization and reducing the incorporation of 15 N‐labeled detritus into plankton biomass, thereby reducing the flux of terrestrial subsidies to higher trophic levels. Our results indicate fire chemically transforms plant detritus and alters the role of aquatic ecosystems in processing and storing carbon. Wildfire may therefore induce shifts in ecosystem functions that cross the boundary between aquatic and terrestrial habitats.

RNA-Binding Proteins: A Role in Neurotoxicity? - Andrea Ocharán-Mercado; Jaqueline Loaeza-Loaeza; Yaneth Castro-Coronel; Leonor C. Acosta-Saavedra; Luisa C. Hernández-Kelly; Daniel Hernández-Sotelo; Arturo Ortega (Neurotoxicity Research, 2023)
Despite sustained efforts to treat neurodegenerative diseases, little is known at the molecular level to understand and generate novel therapeutic approaches for these malignancies. Therefore, it is not surprising that neurogenerative diseases are among the leading causes of death in the aged population. Neurons require sophisticated cellular mechanisms to maintain proper protein homeostasis. These cells are generally sensitive to loss of gene expression control at the post-transcriptional level. Post-translational control responds to signals that can arise from intracellular processes or environmental factors that can be regulated through RNA-binding proteins. These proteins recognize RNA through one or more RNA-binding domains and form ribonucleoproteins that are critically involved in the regulation of post-transcriptional processes from splicing to the regulation of association of the translation machinery allowing a relatively rapid and precise modulation of the transcriptome. Neurotoxicity is the result of the biological, chemical, or physical interaction of agents with an adverse effect on the structure and function of the central nervous system. The disruption of the proper levels or function of RBPs in neurons and glial cells triggers neurotoxic events that are linked to neurodegenerative diseases such as spinal muscular atrophy (SMA), amyotrophic lateral sclerosis (ALS), fragile X syndrome (FXS), and frontotemporal dementia (FTD) among many others. The connection between RBPs and neurodegenerative diseases opens a new landscape for potentially novel therapeutic targets for the intervention of these neurodegenerative pathologies. In this contribution, a summary of the recent findings of the molecular mechanisms involved in the plausible role of RBPs in RNA processing in neurodegenerative disease is discussed.

Intrathecal Administration of an Anti‐nociceptive Non-CpG Oligodeoxynucleotide Reduces Glial Activation and Central Sensitization - C. Leiguarda; A. Villarreal; C. Potilinski; T. Pelissier; M. F. Coronel; J. Bayo; A. J. Ramos; A. Montaner; M. J. Villar; L. Constandil; Pablo R. Brumovsky (Journal of Neuroimmune Pharmacology, 2021)

Aβ42 Peptide Promotes Proliferation and Gliogenesis in Human Neural Stem Cells - A. Bernabeu-Zornoza; R. Coronel; C. Palmer; M. Calero; A. Martínez-Serrano; E. Cano; Alberto Zambrano; Isabel Liste (Molecular Neurobiology, 2019)

Water quality indices for groundwater impacted by geogenic background and anthropogenic pollution: case study in Hidalgo, Mexico - D. A. Rivera-Rodríguez; R. I. Beltrán-Hernández; C. A. Lucho-Constantino; C. Coronel-Olivares; S. Hernández-González; M. Villanueva-Ibáñez; V. Nolasco-Arizmendi; G. A. Vázquez-Rodríguez (International Journal of Environmental Science and Technology, 2019)

Diversity and Phenology of Wild Bees in a Highly Disturbed Tropical Dry Forest “Desierto de la Tatacoa”, Huila–Colombia - C A Poveda-Coronel; D Riaño-Jiménez; J R Cure (Neotropical Entomology, 2018)

Prevalence, intensity and population dynamics of hard ticks (Acari: Ixodidae) on sheep in the humid tropics of Mexico - Karen C. Coronel-Benedett; Nadia Florencia Ojeda-Robertos; Roberto González-Garduño; Francisco Martínez Ibañez; Roger Iván Rodríguez-Vivas (Experimental and Applied Acarology, 2018)

Sphinganine and sphingosine levels and ratio in urine and blood samples from a Catalonian population, Spain - G. Cano-Sancho; S. Marin; V. Sanchis; C. Colom; M.B. Coronel; A.J. Ramos (Food Additives & Contaminants: Part A, 2011)

Daily rhythms in blood and milk lead toxicokinetics following intravenous administration of lead acetate to dairy cows in summer - S. E. Valtorta; M. C. Scaglione; P. Acosta; J. E. Coronel; H. R. Beldomenico; J. C. Boggio (International Journal of Biometeorology, 2006)

Cadmium and Lead Levels in Cow's Milk from a Milking Region in Santa Fe, Argentine - M. R. Rubio; M. E. Sigrist; T. Encinas; E. E. Baroni; J. E. Coronel; J. C. Boggio; H. R. Beldomenico (Bulletin of Environmental Contamination and Toxicology, 1998)